Effectiveness of Cabergoline therapy in hyperprolactinemic infertility - Pitale, Devdatt Laxman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hyperprolactinemia may be associated with ovulatory dysfunction and resultant subfertility. Hyperprolactinemia affects the pulsatile release of GnRH, which in turn impairs the secretion of FSH and LH. It may also affect the endocrine activity of ovarian follicles, resulting into luteal phase defect and ovulatory dysfunction. Hyperprolactinemia may be associated with infertility in up to one-third of women undergoing infertility workup. Women with hyperprolactinemia are generally treated with dopamine receptor agonists to reduce serum prolactin levels and regularisation of menses. The aim of this study was to study the effectiveness of cabergoline therapy in hyperprolactinaemic infertility. Methods: This prospective study was performed from June 2017 to July 2018 in women with Hyperprolactinemic infertility attending the infertility clinic at INHS Patanjali. In this study, 20 women with hyperprolactinemic infertility who satisfied the inclusion and exclusion criteria were started on four week cabergoline therapy. The effectiveness of therapy was evaluated on the basis of normalization of prolactin levels, regularization of menses, reduction in galactorrhea, successful conception and adverse effects if any. Results: The women on Cabergoline therapy showed marked improvement in menstrual irregularity, near normal prolactin levels and reduced galactorrhea. After the four week Cabergoline therapy the frequency of galactorrhea and irregular menses was reduced in 8 (80%) and 14 (93.3) per cent, of women respectively. Successful conception was achieved in 17 (85%) women after regularization of menses with no any major adverse effects. Conclusions: This study shows the effectiveness of cabergoline therapy both on lowering the serum prolactin levels and successful Conception with no any major adverse effects. Cabergoline therapy is a cost effective and safe option in hyperprolactinaemic infertility.